An Analysis of University Students’ Perspective on Online Learning in the Midst of Covid-19 Pandemic - Sujarwo Sujarwo; Sukmawati Sukmawati; Akhiruddin Akhiruddin; Ridwan Ridwan; Suharti Siradjuddin Suharti Siradjuddin (Universitas Pendidikan Ganesha, 2020)
In this study we address and investigate university students’ perspective on utilizing online learning in the midst of COVID-19 pandemic. This research used qualitative descriptive method. The subject of this research were the learners of Elementary School Teacher Education, Physical Education, Sociology Education and English Education Department of Universitas Megarezky in 2019/2020 academic year. The number of respondents was 40 respondents. The research instruments were questionnaire that was obtained by google form through analyzing participants’ response to know their perspective in using online learning and in-depth interview. The study showed that previously, students did not use online learning before the pandemic because learning was conducted in the classroom. In the midst of covid-19 pandemic, the students are interested in using online learning in which can be accessed flexible, anywhere and everywhere. The best application used by lecturers and students was WhatsApp application. It can be concluded that the students’ perspective on online learning had a positive impact in the midst of the covid-19 pandemic.